Perspectives on access to and management of natural resources - Julie Koch (Danish Institute for International Studies (DIIS), 2008)
In understanding inequality in access to natural resources the working paper discusses theories of access and entitlement, different conceptual approaches to institutions, and new global changes and political ecology. Three management approaches are examined: community-based natural resource management, decentralization and right-based frameworks. The strength and the weaknesses of the various approaches are highlighted, and it is argued that there is a need to better combine management and the more conceptual approaches to natural resources.
Keywords: 330; Natürliche Ressourcen; Rohstoffpolitik; Soziale Ungleichheit; Dezentralisierung; Partizipation